Avaliação da correlação entre eletromiografia e a sensação subjetiva da dor - Oliveira, Iraides Moraes (2013)
Pain is an unpleasant sensation associated with actual or potential tissue damage. Pain assessment is very important to establish the efficacy of analgesics, therapies, however, because it is a subjective experience complex and it is necessary a method that quantifies objectively. Biopotentials, such as the electromyographic signals (EMG) may aid in the study of pain. The nociceptive flexion reflex (NFR), which is observed in the biceps femoris muscle with electrical stimulation of the ipsilateral sural nerve has been used as an indicator of physiological nociceptive. Therefore, the objective of this research is to analyze whether there is a relationship between the intensity of electrical stimulation, subjective perception of voluntary and NFR obtained by EMG of the biceps femoris after electrical stimulation of the same side sural nerve. Participated in the experiment 10 healthy males, aged 20-27 years in the Biomedical Engineering Laboratory of Federal University of Uberlândia UFU. In the right lower limb (dominant) the volunteer was positioned on the track retromalleolar outer electrode of the sural nerve stimulation. In the biceps femoris muscle of the same member, the electrode was fixed surface EMG. The stimulus parameters are determined in the equipment Neuropack S1 MEB-9400 Nihon Kohden, which were as follows: 5 rectangular pulse trains with 0.2 ms and 10 ms interval between pulses. The acquisition of electromyographic signals was controlled by software Myosystem-Br1 version 3.5.6. Using a visual analog scale (VAS), was determined and the pain threshold and tolerance level of the subject of research, which were normalized with 0% and 100% respectively. We analyzed the approximate entropy, the area of the EMG signal, the VAS and the RMS (root mean squared) as a function of the intensity of electrical stimulation applied. The approximate entropy was evaluated by means of electromyographic signal, 100 ms before (PréEn) and 200 ms later (PósEn) of electrical stimulation. The data were stored on .txt and analyzed with MatLab, where a specific interface was developed to process the signals collected. There was a statistical analysis based on Pearson\'s correlation coefficient (r), coefficient of determination (r2) and linear regression. There was a strong positive linear correlation of VAS as a function of stimulus, with r = 0.998307 and r2 = 0.9966. The PréEn showed a weak negative linear correlation, with = -0.67741 and r2 = 0.4589 and PósEn a strong negative linear correlation with respect to the stimulus, with r = -0.93315 and r2 = 0.8708. The area showed strong positive linear correlation in relation to the applied stimulus (r = 0.974094 and r2 = 0.9489), and the RMS 200 ms after stimulation (r = 0.97 and r2 = 0.946). Therefore, it was observed that the variables PósEn, RMS and area of flexion reflex are relevant parameters in the correlation of subjective pain.